Incoming And Outgoing Mail Filing Information System Using The View Controller Model At College Institutions - Hasanuddin Sirait; Harmonvikler d. Lumban Raja (Jurnal Mantik, 2021)
Research aims (1) to improve the filing system that is still manual and can facilitate workmanship in inputting mail data (2) as learning the creation of information systems in the form of Web Base using model view controller programming methods. This research was conducted at a college institution. The method used in this study is the collection of data by observing directly on the research object regarding the workings of college institutions in handling the filing of incoming and outgoing letters. Furthermore, the data that has been obtained will be equipped with interview data about existing archiving.From the results of research that has been carried out it can be concluded that with the information system filing incoming le tters and exit letters can help, facilitate the work in filing at college institutions.